Dharma : the Hindu, Jain, Buddhist and Sikh traditions of India - Howard, Veena R. (London ; New York : I.B. Tauris, 2017)
"Dharma is central to all the indigenous religious traditions of India, which cannot adequately be understood apart from it. Often translated as "ethics", "religion" or "religious law", dharma possesses elements of each of these but is not confined to any single category. Neither is it the equivalent of what many in the West might usually consider to be "a philosophy". This much-needed analysis of the history and heritage of dharma shows that it is instead a multi-faceted religious force, or paradigm, that has defined and that continues to shape the different cultures and civilizations of South Asia in a whole multitude of forms, organizing many aspects of life. Experts in the fields of Hindu, Jain, Buddhist, and Sikh studies here bring fresh insights to dharma in terms both of its distinctiveness and its commonality as these are expressed across, and between, the several religions of the subcontinent. Exploring ethics, practice, history, and social and gender issues, the contributors engage critically with some prevalent and often problematic interpretations of dharma, and point to new ways of appreciating these traditions in a manner that is appropriate to and thoroughly consistent with their varied internal debates, practices and self-representations."--
Toward an understanding of dharma : the questions of identity, hybridity, fluidity, and plurality / Veena R. Howard -- Hindu dharma : unity in diversity- a pluralistic tradition / Jeffery D. Long -- Jain dharma : the eternal law of ahimsa / Christopher Key Chapple -- Buddha dharma (dhamma) : "reliable teachings"- according to the Buddha and Buddhism / Rita M. Gross -- Sikh dharam : path of the seeker of truth / Jagbir Jhutti-Johal -- Appendix : Sufism in India / Arthur F. Buehler.
Includes bibliographical references and index.
Keywords: Dharma; Hinduism; Jainism; Dharma (Buddhism); Buddhism; Sikhism; Buddhism; Dharma; Dharma (Buddhism); Hinduism; Jainism; Religion; Sikhism; India -- Religion; India